Molecular analyses of a tyrosinase-negative albino family. - Park, K C (1993)
Sequence analysis of the tyrosinase coding region from an individual with tyrosinase-negative oculocutaneous albinism revealed that the patient was a compound heterozygote. One allele carried a C--> A single-base substitution in codon 355 of exon 3, and the other carried a two-nucleotide deletion in exon 1. The nucleotide substitution caused a putative amino acid change from threonine (ACA) to lysine (AAA), abolishing a signal for N-glycosylation. The two base-pair deletion caused a frameshift, creating a putative premature termination signal at codon 226. The melanocytes from the proband and her affected brother were amelanotic and devoid of measurable tyrosinase activity. Moreover, gel electrophoretic analysis of the immunoprecipitated proband tyrosinase showed that the protein was not processed to the mature glycosylated form, confirming the predicted consequence of the amino acid change. The two-base deletion on the homologous allele was detected only by sequencing genomic DNA. The transcript of this allele was not represented in the cDNA library and could not be detected by PCR mRNA, and the putative truncated protein (approximately 25 kDa) was not present in immunoprecipitates, suggesting that the allele with the missense mutation may be preferentially expressed.